2002
DOI: 10.1046/j.1365-2648.2002.02412.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' attitudes towards clients who self‐harm

Abstract: There is a need for continuing professional development activities to address negative attitudes and provide practical strategies to inform practice and clinical protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
232
4
14

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(266 citation statements)
references
References 20 publications
(20 reference statements)
16
232
4
14
Order By: Relevance
“…Capitalizing on the expertise of the various disciplines may streamline suicide risk assessment, offer improved care for at-risk patients and offer ED providers more time to care for other emergently ill patients. Treating suicidal patients can be burdensome, 27,28,29 and accessed by following the link in the citation at the bottom of the page.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Capitalizing on the expertise of the various disciplines may streamline suicide risk assessment, offer improved care for at-risk patients and offer ED providers more time to care for other emergently ill patients. Treating suicidal patients can be burdensome, 27,28,29 and accessed by following the link in the citation at the bottom of the page.…”
Section: Discussionmentioning
confidence: 99%
“…A small body of qualitative work has demonstrated that ED providers experience negative emotions when working with patients who present with suicide-related concerns, including frustration, lack of confidence and a desire to focus on patients' medical concerns rather than on psychosocial needs. 27,28,29 To date, we are aware of no published qualitative research that has examined ED providers' perspectives on the process of assessing suicide risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] The clinical population are individuals who are diagnosed with an identifiable mental illness. [13] However, it is difficult to accurately diagnose an individual who engages primarily in NSSI with any diagnosis within the American Diagnostic Association.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both Emerson (2010) and Motz (2009) claim that cutting is one of the most common methods of self-harm, though other methods include burning, scratching, headbanging, starvation, drug-taking and intense exercise (Skegg, 2005 harm to a symptom of a personality disorder represents an adequate response to the phenomenon. Furthermore this distinction between the psychiatric classification of eating disorders versus self-harm seems to be reflected in general societal perspectives on these phenomena; whilst eating disorders are widely classified as an illness (Sansone & Levitt, 2002), self-harm is often viewed as attention seeking behaviour (McAllister et al, 2002). This may be important since the way in which people conceptualise a psychological phenomenon may have consequences for the ways in which they behave towards individuals who exhibit it.…”
Section: Introductionmentioning
confidence: 99%